Resolving the conflict between the protection of international investments and the state's right and responsibilty to regulate - McKenzie, Sarah Jenelle (My University, 2017)
This dissertation interrogates whether there is an irresoluble conflict between the traditional form of protection offered to foreign investments under bilateral and multilateral investment treaties and the right and responsibility of states to regulate in the public interest. It examines the criticisms against the traditional form of protection under such treaties, which have been voiced vociferously in the last few years, and contrasts these with the justifications for it. Ultimately, it appears that the protections and mechanisms for enforcement under investment treaties do act to curtail what would otherwise be legitimate exercises of sovereignty by host states and that this can have a significant chilling effect on a state's ability to implement important regulatory initiatives and policies. It also appears, however, that, although there is potential for tension between the protection of investments and the state's right and responsibility to regulate, this potential can be managed. This dissertation analyses the reaction of the South African government to the concerns it has with its investment treaties, which ultimately found expression in the arguably extreme decision to give notice of non renewal of a number of its investment treaties and the adoption of domestic legislation which provides an undeniably diluted form of protection. This reaction leaves much to be desired and will ultimately have negative consequences of its own. It can be contrasted with that of other actors within the international arena who, whilst also harbouring concerns about the potential incursion of investment treaties into their regulatory mandate, have taken proactive and innovative steps to reform and craft their investment protection obligations to ensure that they retain sufficient regulatory space, without attracting the negative consequences of a complete rejection of the prevailing system. States should recognise their ability to tailor their commitments to their specific and evolving needs and take steps to craft legal frameworks that will provide sufficient investment protection without too great an incursion on their regulatory responsibilities.
Submitted in fulfilment of the requirements for the degree: Masters of Laws LLM by Dissertation (Research) Faculty of Commerce, Law and Management – School of Law University of the Witwatersrand, 2017
Keywords: Investments, Foreign--Law and legislation; Treaties